Sustainability through Energy-Efficient Buildings - Shukla, Amritanshu; Sharma, Atul; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
The book covers chapters ranging from introduction to recent technological challenges, case studies of energy-efficient buildings with policy and awareness issues, fundamentals and present status along with research updates and future aspects on topics focusing on energy-efficient construction, materials.
--Introduction to Energy Efficient Building Development and Sustainability -- VVN Kishore, --TERI New Delhi and -- R. K. Singh --Durban University of Technology, Durban, South Africa -- An introduction of Zero Energy Lab as a test bed: concept, features, and application -- --Tingzhen Ming, --Wuhan University of Technology --China, and -- Yong Tao--, College of Engineering and Computing, Nova Southeastern University, 3301 College Avenue, Fort Lauderdale, Florida 33314-7796, USA -- Building Envelops: A passive way to achieve energy sustainability through energy efficient buildings -- Dr Manoj Kumar Srivastava,-- Department of Physics, Army Cadet College, Indian Military Academy, Dehradu, India -- Passive and Low Energy buildings -- --Lu Aye & Amitha Jayalath, --University of Melbourne, Australia -- Energy efficient building construction and Embodied energy -- --R. K. Singh & Ian J. Lazarus--, Durban University of Technology, Durban, South Africa -- BIPV (Building Integrated Photovoltaic) as power generator for energy efficient buildings -- --Karunesh Kant, Amritanshu Shukla, Atul Sharma, --RGIPT Raebareli -- Energy conservation potential through thermal energy storage medium in buildings -- --C. Veerakumar and Sreekumar, --Centre for Green Energy Technology, Pondicherry University, Pondicherry, India -- Silica aerogel blankets as super insulating material for developing energy efficient buildings -- --N. Kevin, Biwole Pascal, and A. Patrick, --Matre de Confrences, Universit de Nice Sophia Antipolis Directeur Dpartement Btiments Polytech Nice Sophia, France -- Heating Ventilation and Air-conditioning (HVAC) systems for energy efficient buildings -- --Karunesh Kant, Amritanshu Shukla, Atul Sharma, --RGIPT Raebareli -- Improving energy efficiency in buildings: challenges and opportunities in the European context -- --Delia D'Agostino, --Directorate C Energy Efficiency and Renewables, Joint Research Centre (JRC) - European Commission, Italy -- Advances in Simulation Studies for developing energy efficient buildings -- --Karunesh Kant, Amritanshu Shukla, Atul Sharma, --RGIPT Raebareli -- Advances in Energy efficient buildings for New and Old buildings -- --A.K. Chaturvedi, Dr. Siddartha Jain, Dr. Deep Gupta, Dr. Mridula, --Roorkee college of Engieering, Roorkee, India -- Role and impact of policy on growth of Green Buildings in India: Impact on sustainability through energy efficient buildings -- --Manish Vaid, --Observer Research Foundation, New Delhi & -- Sanjay Kar, --RGIPT Raebareli -- Energy efficient buildings: Technology to policy and awareness-- Saurabh Mishra, --RGIPT Raebareli.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Environmental / General; Buildings -- Energy conservation; HOUSE & HOME -- Do-It-Yourself -- Plumbing; Electronic books